Comparison of the physiological responses of an oil-pumpkin cultivar and hybrid under different nitrogen supply conditions - Gáspár, Soma Gáspár; Zsombik, László; Veres, Szilvia (Acta Agraria Debreceniensis, 2019)
Cucurbita pepo var. styriaca is known as a medicinal crop among other cucurbits. The benefits of cucurbits fruits are very important in terms of human health, purification of blood, removal of constipation, digestion and supplying energy. The mutant styrian oil-pumpkin (Cucurbita pepo L. convar. Pepo var. styriaca Greb.) exposes a complete lack of lignification of the seed testa. For this reason, this kind of naked pumpkin seed is more consumable as snack than other seeds. The vegetative growth of plants is crucial for fruit production. Nitrogen is the most imperative element for the proper vegetative growth and development of plants which significantly increases and enhances yield and its quality by playing a vital role in the biochemical and physiological functions of plants.Field studies were conducted to study the effect of nitrogen nutrition on certain physiological parameters and their differences between the styrian oil pumpkin hybrid and cultivar (Gleisdorfi Classic cultivar and GL Rustical hybrid). The small block experiment was carried out based on a factorial experiment with a completely randomised block design and four replications in the Research Institute of Nyíregyháza during the summer period of 2017 and 2018. Three different concentrations of nitrogen fertiliser was applied at sowing. Photosynthetic pigments (chlorophyll-a, -b and carotenoids) were analysed as one of the basic factor of efficient photosynthesis. The yields of two genotypes were also measured in all treatments as seed-weight. The contents of photosynthetic pigments were higher in the oil-pumpkin hybrid, mainly the carotenoids in 2018. The vegetation period of 2018 was drier than in 2017, the hybrid oil-pupmkin was more efficient in stress tolerance than the cultivar with higher carotenoids pool. The obtained yield was more pronounced in the oil-pumpkin hybrid than the cultivar in all examined years. The hybrid GL Rustical was more sensitive to nitrogen treatment than the cultivar Gleisdorfi Classic.